The malacopathogenic nematode Phasmarhabditis californica does not affect the survival of earthworms (Lumbricus terrestris and Eisenia fetida) or insects (Galleria mellonella and Tenebrio molitor). Issue 6 (3rd June 2022) - Cutler, James; Rae, Robbie
ABSTRACT: Phasmarhabditis hermaphrodita is a parasitic nematode of terrestrial gastropods that has been formulated into a successful biological control agent used on farms and gardens across Europe. There are reports of members of the Phasmarhabditis genus affecting the survival of non-target organisms under lab conditions e.g. earthworms. Therefore, we exposed two species of earthworm ( Lumbricus terrestris and Eisenia hortensis ) and insect ( Galleria mellonella and Tenebrio molitor ) to a range of doses of P. californica (0, 30 and 150 nematodes per cm 2 ). P. californica did not affect earthworm or insect survival emphasising these nematodes are gastropod parasites that pose no risk to earthworms or insects (based on laboratory trials).